2015
DOI: 10.1080/17449057.2015.1032007
|View full text |Cite
|
Sign up to set email alerts
|

Reserved Seats, Political Parties, and Minority Representation

Abstract: This article seeks to clarify the relationship between reserved seats filled through competitive elections, political parties, and substantive minority representation. It argues that the party affiliation of the minority representative moderates the impact of reserved seats on substantive representation since minority and party constituencies can cross-pressure a representative or, in the case of overlap, can allow her to cater to party and minority interests simultaneously. Drawing on empirical examples, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Quotas and reserved seats constitute other electoral institutions that commend themselves for increasing the number of ethnic and regional minorities in formal politics. Contrary to gender, when it comes to regional and ethnic minorities, reserved seats are more common than party quotas (Htun 2004;Zuber 2015). On the one hand, the mechanism is relatively straightforward, and we can expect a direct impact on the number of minority representatives as a consequence.…”
Section: Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quotas and reserved seats constitute other electoral institutions that commend themselves for increasing the number of ethnic and regional minorities in formal politics. Contrary to gender, when it comes to regional and ethnic minorities, reserved seats are more common than party quotas (Htun 2004;Zuber 2015). On the one hand, the mechanism is relatively straightforward, and we can expect a direct impact on the number of minority representatives as a consequence.…”
Section: Institutionsmentioning
confidence: 99%
“…While ethnic parties can provide a concentrated effort to represent substantive interests of regional and ethnic minorities, there is also a danger that they represent the interests of a particular subgroup and reduce mobilization along other interests that cut across ethnic lines, like poverty. By politicizing ethnic differences, ethnic community leaders and ethnic parties may project social cleavages through an ethnic lens, which may encourage ethnic conflict (Zuber 2015). In this context, claims to representation by ethnic parties (compare Saward 2006), but also the acceptance of these claims by mainstream parties deserve careful study.…”
Section: Candidates Political Parties and Party Leadersmentioning
confidence: 99%
“…For example, in a recent comparative study on the representation of 88 minority groups of 47 countries, Hänni concludes that descriptive representation has a stronger effect on policy outcomes if the minority representatives are also included in government, the legislature is strong, and are backed up by a numerous group (Hänni, 2016). Zuber (2015) demonstrated that political parties may also play a significant role in shaping the outcome of descriptive representation. Minta, in his study about the relationship between legislative oversight and the representation of black and Latino interests in the US Congress, observed that descriptive representation had a significant effect on the racial policy dimension, but not in other policy dimensions, such as welfare (Minta, 2009, p. 210).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…As the previous sections have illustrated, electoral systems already depart from strict equality of voting power in order to protect communities of interests, and including representatives of all politically relevant groups is a normatively desirable goal that aspires to the democratic ideal of collective self-rule. 294 Reserved seats are potentially particularly advantageous for marginalised ascriptive groups as they present the opportunity for members of such groups to "set the agenda". 295 Indeed, in her examination of "the politics of presence", Anne Phillips has noted that the real value of presence lies in the way it may "transform the political agenda" by expanding the range of ideas and rendering visible what was invisible.…”
Section: Reserved Seatsmentioning
confidence: 99%